Censorship in public and school libraries and library activism against banned books - Gómez-Díaz, Raquel; García-Rodríguez, Araceli (Anuario ThinkEPI, 2023)
Book censorship in libraries has risen in a worrying way in recent years, especially affecting public and school libraries, with percentages of censorship increasing year on year. Proposals to ban books are usually made by parents through school or citizen boards, library users, and political and religious groups either because of the subject matter they deal with or due to linguistic, ethnic or religious fundamentalist reasons. In response to this, librarians remain vigilant and show their resistance by denouncing cases or providing legal assistance through professional associations. Other initiatives such as the celebration of Banned Books Week, making banned copies available, placing labels on books to draw attention to what is censored or showing how books are selected in libraries are also being launched.